RECEIVE ALARMS AND FORM ITS DATABASE USING THE AD8232 EKG MODULE (Web of Discoveries: Journal of Analysis and Inventions, 2023)
To organize the data exchange process, we will implement it from the following to the top approach. This involves a process ranging from receiving an ECG to receiving data processed on the website by a doctor. First, the ECG module receives EKG data from the patient and transmits it via USB to the Arduino microcontroller in a sequence - sequence - to the computer. Second, the data collected on the computer is successfully sent and stored on a web server that is displayed over the Internet. For further analysis, the user (in our case, the doctor) is provided, and the doctor, with his own experience, diagnoses the patient. This hardware model was accomplished by connecting different modules and small modules to each other. We will look at devices that play a major role in efficient data transfer and management